Guidelines of calculation and graphical performing the task on the topic "Linear electric circuits of harmonic current" - Rezynkina, M. M.; Kiessaiev, O. H.; Rezynkin, O. L.; Lytvynenko, S. A. (My University, 2020)
The methodical instructions are intended for students of the specialties 141 "Electric Power, Electrical Engineering and Electromechanics", 151 "Automation and computer-integrated technologies", 171 "Electronics" of full-time and distance forms of study.
Keywords: guidelines; calculation and graphical performing; performance purpose; performance order; general provisions; examples; linear electric circuits; harmonic current calculations